2007
DOI: 10.1088/0031-9155/52/15/n04
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of megavoltage CT scan registration settings for thoracic cases on helical tomotherapy

Abstract: This study aims to investigate the settings that provide optimum registration accuracy when registering megavoltage CT (MVCT) studies acquired on tomotherapy with planning kilovoltage CT (kVCT) studies of patients with lung cancer. For each experiment, the systematic difference between the actual and planned positions of the thorax phantom was determined by setting the phantom up at the planning isocenter, generating and registering an MVCT study. The phantom was translated by 5 or 10 mm, MVCT scanned, and reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 9 publications
2
24
0
Order By: Relevance
“…Usually, image registration was based on bony or bony and soft tissue anatomy. The accuracy and precision of the MVCT‐kVCT registration is lower than 1 mm, as has been proved by other authors 10 , 11 . As pitch and yaw deviations cannot be corrected by gantry or automatic couch offsets, the patient was repositioned if these deviations were greater than 3°.…”
Section: Methodsmentioning
confidence: 77%
See 1 more Smart Citation
“…Usually, image registration was based on bony or bony and soft tissue anatomy. The accuracy and precision of the MVCT‐kVCT registration is lower than 1 mm, as has been proved by other authors 10 , 11 . As pitch and yaw deviations cannot be corrected by gantry or automatic couch offsets, the patient was repositioned if these deviations were greater than 3°.…”
Section: Methodsmentioning
confidence: 77%
“…This effect, may be due to several reasons: the couch top is being dragged into the bore by the patient's weight against the longitudinal drive mechanism; (22) there is a mismatch between the CT laser and tomotherapy red lasers, and/or the MVCT slice resolution, as suggested by Hui et al (20) Woodford et al (11) observed that this scan resolution leads to large longitudinal shifts, independently of the combination of fusion technique and registration resolution selected.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the scan range and parameters influence the available information and this can affect the registration precision. 26,27 It should further be understood that registering patient images can be more subjective depending on the anatomical site because anatomical changes in the patient can add a level of complexity and subjectivity that is absent from rigid phantom alignments. The clinical registration precision can be determined using actual patient images, clinical operators, and clinical alignment techniques.…”
Section: Vib1 Spatial/geometry Testsmentioning
confidence: 99%
“…The tumor region was scanned daily, and positioning was done using the integrated registration with the planning CT (19)(20)(21). The megavoltage computed tomography (MVCT) images were extracted from the TomoTherapy data server for every fraction and were imported into iPlan (BrainLAB AG, Feldkirchen, Germany) for review and analysis of primary tumor volume regression.…”
Section: Class Solutionmentioning
confidence: 99%